The Mediating Role of Customer Satisfaction on the Relationship between Service Quality and Consumer Loyalty on the Hospitality Industry - Deandra Vidyanata (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Service quality and customer satisfaction are important predictors that shape customer loyalty in the hospitality industry. The fulfillment of these two things can maintain the sustainability of the organization in the long term. This study aims to examine the effect of service quality on customer loyalty, the effect of service quality on customer satisfaction, customer satisfaction on customer loyalty, and the mediating effect of customer satisfaction on the relationship between service quality and customer loyalty. The population of this research is all consumers of one of 5-star hotels in Jakarta, with purposive sampling method with the criteria of having stayed at the hotel more than 3 times. The results of this study indicate that all hypotheses are accepted,which means that service quality affects consumeraloyalty, service quality affects consumer satisfaction,customer satisfaction affects loyalty, and consumer satisfaction mediates the influence between service quality and consumer loyalty.